INTRODUCTION TO DRAIN HEADER OF THERMAL POWER STATION - JANKAR, Mr. SUNIL; RATHORE, Prof. R S; GUPTA, Prof. ASHOK KUMAR (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
This is about to reduce the cost of distilled water used in the thermal power station then reduce corrosion in the steam pipes, proper designing of steam pipes and selection of a proper insulation material. Everyday thermal power plant uses many liters of water for power generating process. This water first passed through D.M.Plant process. D.M.Plant’s operating cost is the major factors which reduce the profit of power production. And every day in the power plant very much waste of water takes place. To solve this problem we design the drain header that result in less use of D.M.Plant and more use of condensed water. This will help in the problem of shortage of water for the power plant which is located at non raining area or too far from the water source